CAN NLR BE A BIOMARKER FOR MUCOSITIS AND GVHD IN PATIENTS UNDERGOING ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION? - Quadras, Isabella (2021)
Allogeneic hematopoietic stem cell transplantation (HSCT) is the treatment for many diseases, however can induce important complications such as Oral Mucositis (OM) and Graft-versus-Host Disease (GVHD). The neutrophil-lymphocyte ratio (NLR) is a peripheral biomarker of systemic inflammation and an independent prognostic factor in several inflammatory diseases. Objective: The aim of this study was to evaluate the association of NLR with OM and GVHD in patients undergoing allogeneic HSCT. Methods: Patients who underwent  allogeneic HSCT at the Bone Marrow Transplant Service at the Hospital de Clínicas Complex of the Federal University of Paraná were included in the study. Sociodemographic data and blood count were collected from patients' medical records. NLR was calculated and associated with OM and GVHD. Results: 45 patients were included in the study. NLR was considerably higher in patients who had OM and oral GVHD when compared to patients who did not present these conditions, nonetheless no statistically significant difference was observed. Conclusion: Although both OM and GVHD are associated with inflammatory response as well as to the immune system, it was not associated with NLR. A further investigation considering other variables related to the HSCT might find possible association as it could favor patients management and prevention.